Ratio of justice and sense of justice: the spread case of HIV/AIDS in Indonesia - Thahir, Putri Shafarina; Sunaryo, Sidik (Faculty of Law, University of Muhammadiyah Malang, 2024)
This article discusses the integration between the ratio of justice and a sense of justice in strengthening bioethical values ​​and Islamic law. The ratio of justice is based on applicable legal norms, while the sense of justice is based on human feelings or intuition. Justice, one of the values ​​of bioethics, shows no conflict with the Islamic religion, and it is needed because bioethics emphasizes thinking development to determine the good and bad sides or ethical dimensions of biological aspects, including medical matters related to life. By approaching cases through concrete examples such as the spread of HIV/AIDS, which mainly occurs due to infidelity, positive criminal law and Islamic law have different ratios of justice and sense of justice. Sanctions in Islamic law tend to be more severe, with the application of stoning to perpetrators of adultery. However, the balance between the ratio of justice and the sense of justice here must consider the medical and beneficial impacts on society.